2015
DOI: 10.1186/s12944-015-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum lipid levels and prostate cancer severity among Hispanic Puerto Rican men

Abstract: BackgroundWhile obesity and fat intake have been associated with an increased risk of prostate cancer (PCa) aggressiveness and mortality, the association between lipid levels and PCa phenotype remains unclear. Previous reports evaluating this association are inconsistent and highly variable when considering different racial/ethnic groups. There are scarce data regarding this association among Hispanics, and specifically Puerto Rico’s Hispanic men, a population with a higher burden of PCa, metabolic syndrome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…In our cohort, the mean age at PCa diagnosis was 58 years old, particularly in the overweight group, which could suggest an agreement with Hussein [53]. We cannot conclude that FTO is responsible for PCa development at early age in PR, but the poor dietary patterns in this population [29,34,55] may influence the FTO effect on obesity and hence in PCa. Studies in other populations with a high European heritage had suggested that consumption of animal protein, milk and dairy protein might increase the PCa risk by hormonal changes [17,56].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In our cohort, the mean age at PCa diagnosis was 58 years old, particularly in the overweight group, which could suggest an agreement with Hussein [53]. We cannot conclude that FTO is responsible for PCa development at early age in PR, but the poor dietary patterns in this population [29,34,55] may influence the FTO effect on obesity and hence in PCa. Studies in other populations with a high European heritage had suggested that consumption of animal protein, milk and dairy protein might increase the PCa risk by hormonal changes [17,56].…”
Section: Discussionsupporting
confidence: 61%
“…Previous work in our laboratory established that in Puerto Rican overweight men with PCa there was an increased risk for more severe disease and a higher prevalence (2.9 fold) of metastatic disease in those individuals with higher BMI [33]. In addition, in another study, we also found a positive association between PCa severity in Puerto Rican patients and high triglycerides levels [34]. …”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…When we analyzed the correlation of TG and EOC severity, our data suggest that elevated TG levels refer to high cancer severity. Similarly, a previous study found a positive association between triglycerides and prostate cancer severity [ 30 ] . Cancer cells are closely related to lipid molecules, particularly fatty acids, as membrane structures, energy sources and structural regions of related signaling molecules [ 31 ] .…”
Section: Discussionsupporting
confidence: 56%
“…A handful of studies have shown a close link between obesity, serum lipids and prostate cancer [3,4]. Elevated triglycerides (TGs) and low highdensity lipoprotein (HDL) levels were significantly associated with high-grade prostate cancer, albeit this relationship was not consistent between reports [5][6][7][8]. Moreover, low HDL was associated with adverse pathological findings after radical prostatectomy (RP) [9].…”
Section: Introductionmentioning
confidence: 99%